2023
DOI: 10.1002/aenm.202302047
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylamine (TPA)‐Functionalized Structural Isomeric Polythiophenes as Dopant Free Hole‐Transporting Materials for Tin Perovskite Solar Cells

Rajendiran Balasaravanan,
Chun‐Hsiao Kuan,
Shih‐Min Hsu
et al.

Abstract: A new series of triphenylamine (TPA)‐functionalized isomeric polythiophenes are developed as hole transporting materials (HTM) for inverted tin‐based perovskite solar cells (TPSCs). Bithiophene (BT) is first functionalized with two TPA (electron donor; D) at 3 and 5 positions to give two structural isomeric compounds (3BT2D and 5BT2D). The functionalized BT2Ds are then coupled with 3,3′‐bis(tetradecylthio)‐2,2′‐bithiophene (SBT‐14)/3,3′‐ditetradecyl‐2,2′‐bithiophene (BT‐14) to produce structural isomeric polyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…1 Over the past decade, several seminal strategies have been employed to enhance the efficiency of tin perovskite solar cells (TPSCs) from approximately 6% to over 14%, 2–6 including compositional manipulation, 7–9 additive engineering, 10–13 surface modification 14,15 and device architecture design. 16–18…”
Section: Introductionmentioning
confidence: 99%
“…1 Over the past decade, several seminal strategies have been employed to enhance the efficiency of tin perovskite solar cells (TPSCs) from approximately 6% to over 14%, 2–6 including compositional manipulation, 7–9 additive engineering, 10–13 surface modification 14,15 and device architecture design. 16–18…”
Section: Introductionmentioning
confidence: 99%
“…Solution-processed organic–inorganic hybrid perovskite (OIHP) films are promising materials for use in future photovoltaic devices. The stability of OIHP films is one of the key issues to overcome compared with other competing commercial products. It has been observed that OIHP films are very sensitive to the environment conditions and can degrade quickly in the external environment such as light, temperature, etc., , decomposing into metal halides and gases .…”
Section: Introductionmentioning
confidence: 99%
“…The field of organic semiconductors [7,8], in particular, greatly profits from oligo-and polythiophenes, thanks to their optoelectronic properties, such as luminescence, charge carrier mobility and tunability of the HOMO-LUMO energy gap, which can be adjusted by varying both the number of thiophene subunits and the chemical nature and position of substituents on the heteroaromatic rings. For these reasons, some of the most investigated applications of oligo-and polythiophenes are represented by organic lightemitting diodes (OLEDs) [9], organic field-effect transistors (OFETs) [10], organic solar cells (OSCs) and other photovoltaic applications [11,12], and conductivity-based sensors and biosensors [13,14].…”
Section: Introductionmentioning
confidence: 99%